Pengelolaan Supervisi Akademik Pengawas Satuan Pendidikan Di Sd Negeri Madyotaman Kecamatan Banjarsari Kota Surakarta - Sunarso, Sunarso, Prof. Dr. Abdul Ngalim, M.Hum, Dr. A. Fathoni, M.Pd (2017)
The objectives of the research are to describe: 1) the School Supervisor's academic supervision program planning and organizing; 2) the School Supervisor's academic supervision program actuation; and 3) the follow-up of the School Supervisor's academic supervision program at SD Negeri Madyotaman of Banjarsari Sub District of Surakarta Municipality. The type of the research is a qualitative research. The design of the researh is ethnographical design. The research was undertaken at SD Negeri Madyotaman of Banjarsari Sub District of Surakarta Municipality. The data collecting method is done using observation, in-depth interview, and document techniques. The data analysis is done using interactive model consists of three main components, namely data reduction, data display, and verification. The research concludes that: 1) the School Supervisor's academic supervision program planning were done in the form of academic supervision program. The School Supervisor's academic supervision program were organized based on academic supervision's target. The programs were organized in the form of Annual Supervisory Program, Semester Supervisory Program, and then organized more detailly in Academic Supervisory Plan; 2) the School Supervisor's academic supervision program actuation at SD Negeri Madyotaman No. 38 of Surakarta were done in several activities, namely teachers' development, National Education Standard monitoring, and teachers' assessment. The supervision program actuation were done through office conference at teachers' union meeting and classroom visits; and 3) the follow-up of the School Supervisor's academic supervision program consists of 3 (three) points, namely: 1) each team perform coordination and evaluation having accomplishing the program planning to combine them into the whole teachers' program; 2) perform program evaluation in the end of the year which is used as the input for the subsequent year's program; and 3) The supervisor report the evaluation and supervision monitoring results to be used as reflection and reference for the subsequent year's program.